Geological Characteristics of Deep Shale Gas in the Silurian Longmaxi Formation in the Southern Sichuan Basin, China - He, Shun; Qin, Qirong; Li, Hu; Zhao, Shengxian (Frontiers in Earth Science, 2022)
To investigate the geological characteristics and exploration potential of shale gas in the southern Sichuan Basin, we analyze the coupling relationship between the hydrocarbon generation and storage conditions of the Longmaxi Formation and discuss the preservation conditions from the lateral and vertical migration mechanisms of shale gas. According to the results, the organic-rich shale at the bottom was formed in a strongly euxinic and anoxic reducing environment, the oxygen content increased in the upper water body in which the Longmaxi Formation was deposited, and the water body became oxidized. The organic matter type in the shale is dominantly type I kerogen and a small amount of type II1 kerogen. The organic matter content is more than 3.0% and is in the high- to postmature stage. The enrichment of siliceous organisms increases the organic matter and enhances the brittleness of shale, resulting in "superior hydrocarbons and a favorable reservoir". Pyrolysis of organic matter promotes the formation of organic matter pores and dissolution pores, resulting in a coupled “source-reservoir” accumulation control system. The high vertical formation pressure guarantees the sealing of shale and restrains the lateral escape of shale gas. The high-angle intersection of the highly filled fractures and the current crustal stress can effectively enhance the fracture sealing and inhibit the vertical escape of shale gas, forming a three-dimensional effective closure. Hence, the area featuring a short tectonic uplift time, small amplitudes, large-scale underdeveloped fractures, and a high formation pressure coefficient is a favorable area for shale gas exploration, according to the analysis of three-dimensional preservation conditions.